Pengaruh Rasio Keuangan Terhadap Perubahan Laba Bersih pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022 - Wijaya, Khansa Tsabita; Rachmawati, Titiek (CV. ULIL ALBAB CORP, 2025)
This study aims to analyze the effect of financial ratios, namely Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TAT), and Net Profit Margin (NPM), on changes in net profit in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. Using annual financial statement data published by IDX, this research applies multiple linear regression analysis. The results indicate that CR and NPM have a significant positive effect on net profit changes, while DER has a significant negative effect. TAT shows no significant influence. These findings support previous studies and provide new insights into the importance of financial ratio management amid post-pandemic economic conditions.